2014
DOI: 10.1021/am5018682
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Graphite-Reduced Graphite Oxide Core–Sheath Fiber via Direct Exfoliation of Carbon Fiber for Supercapacitor Application

Abstract: A graphite-reduced graphite oxide (rGO) core−sheath structured fiber was synthesized through chemical exfoliation of graphitic carbon fiber. The graphitic carbon fiber was oxidized to form a graphite− graphite oxide core−sheath fiber and followed by thermal exfoliation to form a graphite−rGO core−sheath fiber. The core−sheath fiber with a three-dimensionally (3D) structured rGO sheath possesses a high surface area and pore size around 5.5 nm. A two-electrode supercapacitor constructed with this core−sheath fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…6b shows the CV curves of the CN-RGO-60 electrode with different scan rates (5-80 mV/s). [58][59][60] The areal capacitance of the CN-RGO/nickel foam electrodes decrease with the increase of scanning rates. 56 This result clearly indicates pseudocapacitance from the Faradaic processes contributes to the charge storage.…”
Section: Resultsmentioning
confidence: 99%
“…6b shows the CV curves of the CN-RGO-60 electrode with different scan rates (5-80 mV/s). [58][59][60] The areal capacitance of the CN-RGO/nickel foam electrodes decrease with the increase of scanning rates. 56 This result clearly indicates pseudocapacitance from the Faradaic processes contributes to the charge storage.…”
Section: Resultsmentioning
confidence: 99%
“…CV curves of the fiber supercapacitors based on HPFs and HCFs with the increasing scan rates from 5 to 100 mV s −1 are shown in Figure S5a,c (Supporting Information), respectively. A rectangular shape profile was shared for both HPF and HCF, indicating a typical behavior of electrochemical double layer capacitor . Compared with the HPF, the CV curves for the HCF can better retain a rectangular shape even at a high scan rate of 100 mV s −1 , which revealed a more rapid charge transport and higher rate performance.…”
mentioning
confidence: 87%
“…A rectangular shape profi le was shared for both HPF and HCF, indicating a typical behavior of electrochemical double layer capacitor. [ 21 ] Compared with the HPF, the CV curves for the HCF can better retain a rectangular shape even at a high scan rate of 100 mV s −1 , which revealed a more rapid charge transport and higher rate performance. Note that although the CV curves based on the HPF were slightly deformed with the increasing scan rates due to a relatively low electrical conductivity, a higher capacitive behavior was observed in comparison with the previous reports from the RGO.…”
mentioning
confidence: 93%
“…To improve their electrochemical performances, 3D graphene (3D-G) network (GF@3D-G) was developed on the GF fibers ( Figure 5a) using electrochemical method and this 3D framework can partially overcome the problem of restacking and aggregation of graphene sheets [51]. It was reported that this GF had better electric conductivity of 10 S cm -1 .…”
Section: Graphene Based Fiber Scsmentioning
confidence: 99%